Reconstructing organization : the loungification of society - O'Doherty, Damian (Palgrave Macmillan, 2017)
This unique book breaks original ground in management and organization studies by drawing on over 2½ years of ethnographic study in a major UK international airport group. Much has been written about the 'McDonaldisation' or 'Disneyization' of society, but few have been attentive to what the author terms 'Loungification of society'. A minor mode of organization, but one whose effects are likely to become ever more profound, this study shows how management and organization is itself being reconstructed and reshaped by way of loungification. Drawing on critical management studies, actor-network theory, and debates in contemporary anthropology around the so-called ontological turn, Reconstructing Organization enacts a veritable experiment in business and management studies. Who are these coming loungers? What do they want? Can we manage them? Or will they soon capture us with their talking chairs and 'crinicultural' politics?- Resumé vydavatel
Keywords: sociologie organizace -- Velká Británie; etnografie; management; organizational sociology -- Great Britain; ethnography; elektronické knihy; monografie; electronic books; monographs